First contribution of the excavation and chronostratigraphic study of the Ruways 1 Neolithic shell midden (Oman) in terms of Neolithisation, palaeoeconomy, social‐environmental interactions and site formation processes. (24th November 2019) - Berger, J. F.; Guilbert‐Berger, R.; Marrast, A.; Munoz, O.; Guy, H.; Barra, A.; López‐Sáez, J. A.; Pérez‐Díaz, S.; Mashkour, M.; Debue, K.; Lefèvre, C.; Gosselin, M.; et al.
Abstract : The NeoArabia project tries to understand how environmental, social, economic and technological factors work in concert to influence settlement and abandonment along a latitudinal transect of 1200 km from UAE to southern Oman. This region was affected by wide north–south variations in the Indo‐Arabian monsoon, marine upwelling activity and eustatic variations in the Mid‐Holocene. On the local settlement scale, this transect is based on fine stratigraphic excavations and permits the reconstruction of the site formation processes and site catchment analysis. A large number of studies have been conducted on the Ruways‐1 site, focusing on a deep stratified sequence corresponding to three millennia of occupation. These studies include on‐site climate‐environmental signal analysis, local palaeogeography and environmental reconstruction, reservoir effect studies, typo‐technological studies, palaeoeconomic strategies, anthropological studies, sclerochronological studies and, finally, site formation processes, the understanding of which makes it possible to explain the potential and limits of the archaeological excavation. The first results confirm the richness of these archaeological archives for documenting the socio‐environmental dynamics, but also the richness of its complex sedimentary structure and the importance of conducting fine and multidisciplinary excavations to answer questions about the rhythms and functions of occupations and the causalities of socio‐environmental changes.